MEMBANGUN AKSI KEMANUSIAAN MELALUI VISUALISASI PESAN DENGAN LOMBA POSTER - Agustina Fitrianingrum; David Cantona; Chris Chris; David Pramono; Eko Pratama Sinaga; Elvin Elvin; Jevon Junanto; Leo Leo; Nelson Nelson; Rifki Rifki; Robin Robin (National Conference for Community Service Project (NaCosPro), 2020)
Aggressive treatment such as bullying, discrimination, racism, and acts of intolerance is very easy to occur on social media today. Negative behavior can cause distress or dangerous behavior, which affects social, mental health, educational success, physical safety, and others. The public needs to be educated so that they can behave politely not only in direct social communication but also when interacting using social media. The role of modern communication technology as a medium of education is very significant. Therefore, it can be used especially to educate adolescents, therefore anti-bullying poster competition and other aggressive behavior for the public in were chosen. Even though a very short-term program in two weeks, the competition was attended by 6 participants, 5 of whom were students and a high school student not only from Batam but also other areas in Indonesia. Judging based on the originality posted on Instagram.